A laboratory investigation into rock physics and fracture potential of the Woodford shale, Anadarko Basin, Oklahoma - Harris, Dustin Matthew (Kansas State University, 2017)
The Woodford shale in west-central Oklahoma is an organic and silica rich shale that is a prolific resource play producing gas and liquid hydrocarbons (Gupta et al., 2013). Unconventional shale wells are only producible due to modern hydraulic fracturing techniques. Production surveys from unconventional reservoirs show significant variability between wells and even between fracking stages (Kennedy, 2012). The production potential of a particular shale appears to be related to its brittleness and kerogen content "sweetness". Thus, brittleness analysis becomes important when choosing which shales to produce. A rocks brittleness index can be related directly to elastic properties derived from P- and S-wave velocities, as well as, its specific mineral makeup. This project's main focus is to determine the elastic rock properties that affect or relate to Woodford shale brittleness and how they relate to the rock's specific mineral makeup and kerogen content. Measurements to determine elastic properties, based on ultrasonic laboratory testing, were conducted on available Woodford cores. The estimated elastic moduli were evaluated via cross-plotting and correlation with a variety of rock properties. Elastic properties are of essential relevance to forward seismic modeling in order to study seismic response. Mineral makeup, determined via XRD and XRF analyses done by Kale Janssen (2017), was used to calculate a mineral-based brittleness index for comparison with the elastic moduli. Evaluation of the elastic moduli assisted in determining which elastic properties directly relate to the brittleness of the shales and, in turn, to geomechanical aspects. These properties were correlated with data from previous studies including mineral percentages, total organic content (TOC), and thermal maturity. These correlations were used to determine which elastic properties best predict a rock's brittleness index. The calculated brittleness was used to develop a brittleness index map of the Woodford Formation.
Keywords: Geology; Geophysics; Mineralogy; Brittleness index; Woodford; Shale